Practice Standard for Work Breakdown Structures - Third Edition - Institute, Project (Project Management Institute, 2019)
The work breakdown structure (WBS) is an essential component of the planning process of all project types, whether external or internal facing, regardless of industry or discipline. The WBS organizes the total scope of a project and reflects the work specified for the approved project scope. The WBS serves as an essential tool for the project team to overcome large project uncertainties. The WBS is a key input to the project's schedule, budget, risk, and performance tracking and serves as a cross-discipline foundation upon which to report project status and progress in a unified and standard manner. The WBS also functions as a mechanism to balance management's need for control through the appropriate level-of-detail representation. As a comprehensive update to the Practice Standard for Work Breakdown Structures - Second Edition, the third edition applies the WBS to the predictive, iterative, incremental, and agile project life cycles; it also explores several different types of decomposition in practice today. The Practice Standard for Work Breakdown Structures - Third Edition aligns with other recent PMI standards, including A Guide to the Project Management Body of Knowledge (PMBOK® Guide) - Sixth Edition. This practice standard provides practitioners with a useful tool to create a valuable, high-quality WBS for portfolios, programs, or projects.